Substrate Stiffness Modulates the Growth, Phenotype, and Chemoresistance of Ovarian Cancer Cells - Fan, Yali; Sun, Quanmei; Li, Xia; Feng, Jiantao; Ao, Zhuo; Li, Xiang; Wang, Jiandong (Frontiers in Cell and Developmental Biology, 2021)
Mechanical factors in the tumour microenvironment play an important role in response to a variety of cellular activities in cancer cells. Here, we utilised polyacrylamide hydrogels with varying physical parameters simulating tumour and metastatic target tissues to investigate the effect of substrate stiffness on the growth, phenotype, and chemotherapeutic response of ovarian cancer cells (OCCs). We found that increasing the substrate stiffness promoted the proliferation of SKOV-3 cells, an OCC cell line. This proliferation coincided with the nuclear translocation of the oncogene Yes-associated protein. Additionally, we found that substrate softening promoted elements of epithelial-mesenchymal transition (EMT), including mesenchymal cell shape changes, increase in vimentin expression, and decrease in E-cadherin and β-catenin expression. Growing evidence demonstrates that apart from contributing to cancer initiation and progression, EMT can promote chemotherapy resistance in ovarian cancer cells. Furthermore, we evaluated tumour response to standard chemotherapeutic drugs (cisplatin and paclitaxel) and found antiproliferation effects to be directly proportional to the stiffness of the substrate. Nanomechanical studies based on atomic force microscopy (AFM) have revealed that chemosensitivity and chemoresistance are related to cellular mechanical properties. The results of cellular elastic modulus measurements determined by AFM demonstrated that Young’s modulus of SKOV-3 cells grown on soft substrates was less than that of cells grown on stiff substrates. Gene expression analysis of SKOV-3 cells showed that mRNA expression can be greatly affected by substrate stiffness. Finally, immunocytochemistry analyses revealed an increase in multidrug resistance proteins, namely, ATP binding cassette subfamily B member 1 and member 4 (ABCB1 and ABCB4), in the cells grown on the soft gel resulting in resistance to chemotherapeutic drugs. In conclusion, our study may help in identification of effective targets for cancer therapy and improve our understanding of the mechanisms of cancer progression and chemoresistance.